Legal status of young scientists in the Russian Federation - A. A. Vasiliev; B. E. Karavanov (Правоприменение, 2024)
The subject. The article presents a comprehensive analysis of the legal status of young scientists in the Russian Federation, taking into account the needs of the Russian scientific society for the reproduction of the scientific knowledge.The purpose of the research is to confirm or to reject the hypothesis of the necessity of the specific legal status of the young scientists in Russian academic law.Methodology. The formal legal method, the method of comparative legal analysis and method of systemic approach were used in the article.The main results. The research proves that the modern Russian academic community is in need of the young scientists due to the aging of the community. According to statistics, the lack of social guarantees and the low prestige of the academic profession result in a low percentage of PhD graduates in the recent years. The study concludes that there is no systematic approach to the definition of the status of a young scientist in the current Russian law. Although attempts to formalize the legal status of the young scientists have been made, they have so far not led to significant results. The authors conclude that the current legislation governing the legal status of young scientists should be harmonised. Analysis of the current legislation on the legal status of young scientists also reveals a number of complex issues. Social guarantees for young scientists, presented in the form of social housing, affect only a small proportion of the scientific community, while there are no laws granting preferential loans for young scientific workers. The participation of young scientists in grant support competitions is complicated due to the lack of a unified approach. Specific problems are faced by female scientists. A partial solution to the problem of the low prestige of the profession for both scientific and pedagogic workers, according to the authors of the article, lies in the foundation of a unified federal system of guarantied wages for such workers.Conclusions. Researchers conclude that a consistent approach to the legal status of young scientists and social guarantees, according to such status, can ensure the stable growth of young people in the sphere of scientific activity. In order to enhance the prestige of the profession of scientist among young people and to prevent the lack of scientific and pedagogical workers, researchers consider it necessary to take a number of measures, such as legal enshrinement of the status of a young scientists, development of a system of social guarantees, search for a new ways to measure the scientific activity of employees, formation of a stable system of postgraduate studies and creation of comfortable working conditions for young scientists.